Pelatihan Penggunaan Aplikasi Mendeley Bagi Mahasiswa Untuk Membuat Daftar Pustaka - R. Mahdalena Simanjorang; Agustina Simangunsong (Cv. Utility Project Solution, 2023)
In the world of education there are several components needed so that existing activities can run well. Namely by making scientific work both lecturers and students. Scientific work that is made must of course be in accordance with established rules so that it is recognized by the academic section which can later be used by other people who cite data such as students who will carry out the preparation of a thesis or people who want to adopt a policy or rule in the development of an institution. their company. So to make a scientific paper must pay attention to the rules in writing. For example, making scientific work must use good and correct language so that it can be more easily understood by readers or people who will cite the scientific work. In fact, there are many obstacles in the making of a scientific paper, namely the writing of each paragraph that is not continuous, the wrong way to do citations of other people's work and not being able to make references to the scientific work. The method used is lectures, and direct practice of operating Mendeley applications. The purpose of carrying out this Community Service activity is to help students understand writing references properly according to predetermined rules and be able to make citations correctly using the Mendeley application.